Modulation of Cytokine Response of Pneumonic Foals by Virulent Rhodococcus equi - Giguère, Steeve (American Society for Microbiology, 1999)
The ability of Rhodococcus equi to induce pneumonia in foals depends on the presence of an 85- to 90-kb plasmid. In this study, we evaluated whether plasmid-encoded products mediate virulence by modulating the cytokine response of foals. Foals infected intrabronchially with a virulence plasmid-containing strain of R. equi had similar gamma interferon (IFN-γ) and interleukin-12 (IL-12) p35 but significantly higher IL-1β, IL-10, IL-12 p40, and tumor necrosis factor alpha (TNF-α) mRNA expression in lung tissue compared to foals infected with the plasmid-cured derivative. IFN-γ mRNA expression levels in CD4(+) T lymphocytes isolated from bronchial lymph nodes (BLN) were similar for the two groups of R. equi-infected foals on day 3 postinfection. However, on day 14, in association with pneumonia and marked multiplication of virulent R. equi but with complete clearance of the plasmid-cured derivative, IFN-γ mRNA expression in BLN CD4(+) T lymphocytes was significantly (P < 0.001) higher in foals infected with the plasmid-cured derivative. These results suggests an immunomodulating role for R. equi virulence plasmid-encoded products in downregulating IFN-γ mRNA expression by CD4(+) T lymphocytes.